Peran pendidikan Islam dalam membentuk karakter peserta didik yang baik - Muzaki, Miftakhul (Maliki Interdisciplinary Journal, 2024)
Islamic education has a crucial role in forming character and positive values in students. This article analyzes the influence of Islamic education on social transformation, highlighting various perspectives and challenges that need to be overcome. Islamic religious education aims to form noble morals and piety, preparing individuals to face moral and social challenges in everyday life. The research method uses a literature review to understand the development of knowledge on this topic. In the discussion, the role of Islamic education in shaping the character of students is explained, including the emphasis on religious principles, appreciation in moral education, and motivation from life after death. Character education from an Islamic perspective emphasizes the formation of positive attitudes and noble morals, which are encouraged by religious teachings. In conclusion, Islamic education is recognized as an important factor in forming disciplined and moral character in students, with educators playing a key role in conveying these values and practicing them in everyday life.